An analysis of Bank Islam Malaysia Berhad financial performance for the 5 years period 2005-2009 / Nor Hanini Mohd Khalid - Mohd Khalid, Nor Hanini (Faculty of Business and Management, 2011)
This paper will provide evidence whether the performance of Bank Islam Malaysia Berhad have any differences within five years financial statement. Other than that, the expectation in this study is that Bank Islam Malaysia Berhad will show the improvement for each year due to their banking activities and also the other activities that Bank Islam Malaysia Berhad involved. Moreover, this study attempts to show that the there is a performance of Bank Islam even they do not involve conventional activities like interest charges. Therefore, this study is to evaluate the performance of Bank Islam Malaysia Berhad between 2005 and 2009 through examine both management of asset and efficient use of resources that will be tested by banks capital structure and solvency ratio, return on investment ratio and operating performance ratio.